Eradicating Problems In The American Public Education System: Contrasting American and British Education Systems – Does Centralisation Fare Well? - Jenkins, Michael (2012)
Thomas Welsh and Noel McGinn published an article in 1999 debating the issues around decentralisation in education. The aim of the study was to criticize centralisation and the stiff control over schools and decision making for educational institutions. While many points were made for decentralisation, there were overwhelming supporting points for centralisation. One of the key points made is that centralisation improves the quality of education through standardised content and overall provision of operations in education. The duo notes that government, in most countries set the regulations in which for quality assurance, employ regulators that monitor quality control. To this day, many countries still employ this system of control on their educational systems with the likes of France, Poland, Austria, China, and the United Kingdom. The lack of various decision making bodies allows for smoother and more fluid like decision making. The United States boasts more than 13,500 school districts compared to the United Kingdom’s school district. In addition, the American public education system is losing its ability to prepare American students for the global workforce. The recent international data shows that U.S. students are lagging far behind students in other industrialized nations. U.S. students scored “below average” in math on the Programme for International Student Assessment examination placing the U.S. 25th out of the 34 Organisation for Economic Co-operation Development participant nations. Only 69 per cent of teenagers finish high school in the required years, while only 40 per cent of young people hold an associate’s or higher college degree and totally half of U.S. employers report a gap between their needs and the skills of their workforce (StudentsFirst, 2012). While students fail to keep up academically, the barrelling economy forces the hand of local governments to make even deeper cuts to education (StudentsFirst, 2012). Over the last three decades, the United States has faces millions ($130) in budget cuts Data from the US Department of Education provides information that government has not been allocating the needed resources for the betterment of education system through its efforts to combat disjointed processes by introducing a national curriculum. Daring five years back, 45 states in the US have faced budget deficits totalling more than $130 billion. One of those states, Colorado cut $260 million from public education that is approximately $400 per registered student. Another state faced with hardship found a slight resolution: the state of Georgia found light to a dim situation with its $4.2 billion shortfall; the 13th state found resolve in slicing $403 million from K-12 funding; Illinois cut $311 million from its education budget; California—which ranks last in per-student K-12 spending—addressed a $17.9 billion shortage by cutting billions from public. (StudentFirst, 2012). The question of late has been, “How, and what can we do to save our schools?"